PELATIHAN GURU SMK MUHAMMADIYAH 4 SLIPI JAKARTA MENGENAI BUSINESS LETTER BERBAHASA INGGRIS - Ulfa, Rima Novia (Jurnal Pengabdian dan Kewirausahaan, 2018)
The aim of this study is to provide training on the technique of making a business letter in English for teachers of SMK Muhammadiyah Slipi Jakarta. Business letter is a letter that is used by a person, organization or institution that deliver business messages in writing to the other party by using a specific media whether it is sending via postal mail, faksmilie, telephone or the internet. The activity of writing a business letter is seen as simple and easy work, but to do it optimally of course required expertise is needed. To write business letter does not require special skills as a writer of novels, poetry, short stories or other literary works, because essentially a business letter is not a literary work. Nonetheless, to wite a good business letter is often not as simple as people imagine, because there are certain rules and habits that are generally applicable and must be met by each author of the letter. Therefore, the words and sentences in the letter should be prepared effectively and efficiently. The accuracy and detail are needed to ensure the contents of the letter are intended by the sender.  Therefore, the outcomes is that the teachers in SMK Muhammadiyah 4 can teach his or her students SMK Muhammadiyah 4 how to create a business letter in English that is good and right so that later after they graduate it can be applied upon entering the workforce. Keywords: Business letter, Teacher Training, Vocational School